Pidana Mati Bersyarat dalam KUHP Baru: Analisis Pengaturan Masa Percobaan dan Konversi Pidana Mati dalam Perspektif HAM dan Asas - Muhammad Faras Abyan (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
Criminal sanctions in Indonesian criminal law are regulated in Article 10 of the Criminal Code (KUHP), which includes the death penalty as one of the principal punishments. However, its implementation has long generated serious debate, as the execution of the death penalty is often viewed as lacking legal certainty. A significant change emerged with the enactment of Law Number 1 of 2023 concerning the Criminal Code, which repositions the death penalty from a principal punishment to a special sanction imposed alternatively through a conditional death penalty mechanism with a 10-year probation period. This study, using a normative juridical approach and literature review, aims to analyze the urgency of this regulation. The findings indicate that if the convicted person demonstrates good behavior during the probation period, the death sentence may be commuted to life imprisonment with the approval of the President after considering the opinion of the Supreme Court. Although this mechanism is presented as a form of humanization and reform of the criminal justice system, the provision in Article 100 paragraph (4), which uses the phrase “may,” creates legal uncertainty regarding whether the sentence will actually be converted. This uncertainty is further compounded by the lengthy probation period and the absence of a clear time limit for the President to issue such a decision. Consequently, this framework reflects both philosophical and juridical ambiguity: while it is framed as a reform, it simultaneously preserves the existence of the death penalty, which may conflict with the principle of the right to life as an absolute human right.